Karakteristik Kimia dan Sensori Bakso Goreng Menggunakan MDM (Mechanically Deboned Meat) Ayam - Nadia Fitriana; Lia Amalia; Siti Aminah (Universitas Djuanda, 2024)
ABSTRACT MDM Chicken is meat produced by separating the remaining meat on the back, head, and neck. Chicken MDM has a paste texture, fibrous, contains muscle or tendons, fat, and connective tissue. Chicken MDM is usually used as an ingredient to make meatballs, sausages, corned beef, and nuggets. The purpose of this study was to utilize chicken MDM to make fried meatballs at a more economical price. This study used a one-factor complete randomized design (CRD) design with 4 levels and 2 repetitions, with the treatment levels of chicken MDM to tapioca (30%: 44%), (40%: 34%), (50%: 24%), and (60%: 14%). Product analysis includes chemical tests including water content, ash content, protein content, and fat content, and sensory and hedonic quality tests including color, aroma, taste, texture, and overall. Data analysis used was ANOVA with Duncan's further test. The results of chemical analysis research gave a significant effect on water content, ash content, fat content and protein content. The sensory quality test significantly influenced texture, color, aroma, and taste. Hedonic test significantly affects texture, aroma, taste and overall. Keywords: MDM Chicken, fried meatballs, cemical analysis, sensory and hedonic. ABSTRAK MDM ayam adalah daging yang dihasilkan dengan cara memisahkan sisa daging pada punggung, kepala, dan leher. MDM ayam memiliki tekstur berupa pasta, berserat, mengandung otot atau urat, lemak, dan jaringan pengikat. MDM ayam biasanya digunakan sebagai bahan untuk membuat bakso, sosis, kornet, dan nugget. Tujuan dari penelitian ini ialah pemanfaatan MDM ayam untuk pembuatan bakso goreng dengan harga yang lebih ekonomis. Penelitian ini menggunakan desain rancangan acak lengkap (RAL) satu faktor dengan 4 taraf dan 2 kali pengulangan, dengan taraf perlakuan MDM ayam banding tapioka (30% : 44%), (40% : 34%), (50% : 24%), dan (60% : 14%). Analisa produk meliputi uji kimia meliputi kadar air, kadar abu, kadar protein, dan kadar lemak, dan uji mutu sensori dan hedonik meliputi warna, aroma, rasa, tekstur, dan overall,. Analisa data yang digunakan adalah ANOVA dengan uji lanjut Duncan. Hasil penelitian analisa kimia memberikan pengaruh nyata terhadap kadar air, kadar abu, kadar lemak dan kadar protein. Pada uji mutu sensori berpengaruh nyata terhadap tekstur, warna, aroma, dan rasa. Uji hedonik berpengaruh nyata terhadap tekstur, aroma, rasa dan overall. Kata kunci: MDM ayam, bakso goreng, analisa kimia, mutu sensori dan hedonik.